Using e-scaffolding to develop students' scientific reasoning through inquiry-based learning - S. Koes Handayanto; S. Fawaiz; A. Taufiq (Russian State Vocational Pedagogical University, 2023)
Introduction. Through inquiry-based learning (IBL), scaffolding is provided to help students develop their scientific reasoning (SR). However, the results obtained by students vary depending on their prior knowledge because the strategies of scaffolding vary on demand. Therefore, the different levels of scaffolding should be provided to all students based on their prior knowledge to facilitate their internalisation of new information in the classroom.Aim. The present research aimed to examine students' SR in a course involving two electronic scaffolding levels (e-scaffolding) in IBL.Methodology and research methods. The authors conducted a mixed-methods explanatory study followed by semi-structured interviews and think-aloud exercises with two classes (experimental and control) of 64 physics students in Indonesia for eight weeks. The authors collected the quantitative data by testing their prior knowledge and SR and obtained the qualitative data from the interviews and the think-aloud exercises, learning activities, photos, videos, and teachers' notes. ANOVA analysis of the quantitative data and thematic analysis of the qualitative data were performed.Results and scientific novelty. To our knowledge, our research marks the first instance of providing scaffolding with a tiered level option, a feature previously limited to a single level. It was found that there were significant differences in students' SR based on students' prior knowledge of the subject. E-scaffolding developed more on SR for students with low prior knowledge. Taking notes as a habit and switching roles during experiments helped improve students' SR. It was observed that the students with low prior knowledge still needed e-scaffolding buttons to master physics concepts. Meanwhile, the students with high prior knowledge employed e-scaffolding buttons only to answer task completion.Practical significance. Based on the research findings, the tiered e-scaffolding produced in this work opens a new potency to be applied by physics teachers to enhance student' SR. Additionally, educational technology developers may consider tiered e-scaffolding designs to provide an adaptive system.